Sea-spray regulates sulfate cloud droplet activation over oceans - Fossum, Kirsten N.; Ovadnevaite, Jurgita; Ceburnis, Darius; Preißler, Jana; Snider, Jefferson R.; Huang, Ru-Jin; Zuend, Andreas; O’Dowd, Colin (Nature Research (part of Springer Nature), 2020)
Sulfate aerosols are typically the dominant source of cloud condensation nuclei (CCN) over remote oceans and their abundance is thought to be the dominating factor in determining oceanic cloud brightness. Their activation into cloud droplets depends on dynamics (i.e. vertical updrafts) and competition with other potential CCN sources for the condensing water. We present new experimental results from the remote Southern Ocean illustrating that, for a given updraft, the peak supersaturation reached in cloud, and consequently the number of droplets activated on sulfate nuclei, is strongly but inversely proportional to the concentration of sea-salt activated despite a 10-fold lower abundance. Greater sea-spray nuclei availability mostly suppresses sulfate aerosol activation leading to an overall decrease in cloud droplet concentrations; however, for high vertical updrafts and low sulfate aerosol availability, increased sea-spray can augment cloud droplet concentrations. This newly identified effect where sea-salt nuclei indirectly controls sulfate nuclei activation into cloud droplets could potentially lead to changes in the albedo of marine boundary layer clouds by as much as 30%. The research leading to these results has received funding from SFI under MaREI; the European Union’s Seventh Framework Programme (FP7/2007–2013) project BACCHUS under grant agreement n_603445; Spanish Ministry of Economy and Competitiveness (MINECO) as part of the PEGASO (Ref.: CTM2012-37615) and BIONUC (Ref: CGL2013-49020-R) projects. The Antarctic cruise that led to this study was organised by R. Simo and M. Dall’Osto from the Institut de Ciéncies del Mar (CSIC), Barcelona, Catalonia, Spain. peer-reviewed